2011
DOI: 10.1017/s0022112010004611
|View full text |Cite
|
Sign up to set email alerts
|

The motion, stability and breakup of a stretching liquid bridge with a receding contact line

Abstract: The complex behavior of drop deposition on a hydrophobic surface is considered by looking at a model problem in which the evolution of a constant-volume liquid bridge is studied as the bridge is stretched. The bridge is pinned with a fixed diameter at the upper contact point, but the contact line at the lower attachment point is free to move on a smooth substrate. Experiments indicate that initially, as the bridge is stretched, the lower contact line slowly retreats inwards. However at a critical radius, the b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 35 publications
4
69
0
Order By: Relevance
“…Here, the drop size is almost two orders of magnitude smaller than in the first two regimes, which Qian et al 24 attributed to a fast receding contact line with a speed approaching u w . However, in volume-controlled deposition, the dispensed-drop size did not exhibit the same sensitivity to the needle retraction speed in the parameter range studied by Qian and Breuer 25 . Thus, our study is motivated, in part, by seeking to answer whether it is possible to influence-by purely geometric means-the dynamics in volume-controlled deposition, so that one may achieve comparable sensitivity as in the pressurecontrolled case, to achieve small-drop deposition.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Here, the drop size is almost two orders of magnitude smaller than in the first two regimes, which Qian et al 24 attributed to a fast receding contact line with a speed approaching u w . However, in volume-controlled deposition, the dispensed-drop size did not exhibit the same sensitivity to the needle retraction speed in the parameter range studied by Qian and Breuer 25 . Thus, our study is motivated, in part, by seeking to answer whether it is possible to influence-by purely geometric means-the dynamics in volume-controlled deposition, so that one may achieve comparable sensitivity as in the pressurecontrolled case, to achieve small-drop deposition.…”
Section: Introductionmentioning
confidence: 77%
“…Minimizing the dispensed-drop size relative to the needle diameter is central to surface patterning based on direct-write lithographic techniques 3,23 . Recent studies of contact-drop dispensing have shown that the deposited drop size is influenced by the needle retraction speed, needle-tip size, surface characteristics, and dispensing control parameters 24,25 . Interestingly, the deposited drop volume in pressure-controlled and volume-controlled dispensing behave differently with the needle retraction speed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations